2014
DOI: 10.1088/2041-8205/787/2/l23
|View full text |Cite
|
Sign up to set email alerts
|

Warm Molecular Gas in Luminous Infrared Galaxies

et al.

Abstract: We present our initial results on the CO rotational spectral line energy distribution (SLED) of the J to J−1 transitions from J = 4 up to 13 from Herschel SPIRE spectroscopic observations of 65 luminous infrared galaxies (LIRGs) in the Great Observatories All-Sky LIRG Survey (GOALS). The observed SLEDs change on average from one peaking at J ≤ 4 to a broad distribution peaking around J ∼ 6−7 as the IRAS 60-to-100 µm color, C(60/100), increases. However, the ratios of a CO line luminosity to the total infrared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 47 publications
11
113
1
Order By: Relevance
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 56%
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 56%
“…Following this scheme, we find that ULIRGs whose SLED increases with increasing J tend to have warm color indices, those with decreasing SLEDs (i.e., SLED peaking at  J 6) have cold color indices, and those displaying flat SLEDS have intermediate color indices. Thus, the shape of the SLED appears to be influenced by the physical properties (e.g., temperature) of the underlying radiation field, which was also noted by Lu et al (2014) for their sample of LIRG galaxies. Finally, we note that an AGN (i.e., warm ULIRGs) will shift the peak of the SLED to higher J transitions, which may be a contributor to both higher C(60/100) colors and warmer SLEDs.…”
Section: Co Sled Modelingmentioning
confidence: 57%
“…GOALS 14 is a multi-wavelength survey aimed at understanding the physical conditions and activity in the most luminous galaxies in the local universe. The data set includes spectroscopic and imaging observations in the infrared from Spitzer (Petric et al 2011;Inami et al 2013;Stierwalt et al 2013, J. M. Mazzarella et al 2015, in preparation), and Herschel (DiazSantos et al 2013, 2014Lu et al 2014), GALEX, and Hubble Space Telescope (HST) UV, optical, and near-infrared imaging (Howell et al 2010;Haan et al 2011;Kim et al 2013, A. S. Evans et al 2015, Chandra X-ray observations (Iwasawa et al 2011), and a suite of ground-based radio and sub-millimeter observations (e.g., Leroy et al 2011;BarcosMuñoz et al 2015, R. Herrero-Illana et al 2015. These observations collectively trace the obscured and unobscured activity and constrain the structural properties and merger stages of these systems.…”
Section: Goalsmentioning
confidence: 99%